The interpretation complying with EU law manifested in the case law unifying judgment No. 15/2013 of the Portuguese Supreme Court of Justice - Machado, Carla (2016)
This article aims to address the interpretation that has been made by Portuguese courts in relation to the concept of “communication of the work to the public” enshrined in Article 3 (1) of Directive 2001/29/EC of the European Parliament and of the Council of 22 May 2001, duly transposed into the Portuguese legal order by Law No. 50/2006 of 24 August, which culminated in the drafting of the case law unifying judgment No. 15/2013. By verifying its content and analysing the case law of the Court of Justice of the European Union (hereinafter CJEU), concerning the interpretation of that concept, we conclude that the said case law unifying judgment does not comply with EU law. Therefore, we will list, on the one hand, the inherent consequences regarding the upkeep of the interpretation that has been held by the Portuguese judicial authorities and, on the other, we will suggest solutions for the resolution of similar cases by appealing to the principle of conforming interpretation.